Effect of a diet rich in galactose or fructose, with or without fructooligosaccharides, on gut microbiota composition in rats - Mhd Omar, Nor Adila; Dicksved, Johan; Kruger, Johanita; Zamaratskaia, Galia; Michaëlsson, Karl; Wolk, Alicja; Frank, Jan; Landberg, Rikard (Frontiers in Nutrition, 2022)
Recent studies suggest that a diet rich in sugars significantly affects the gut microbiota. Adverse metabolic effects of sugars may partly be mediated by alterations of gut microbiota and gut health parameters, but experimental evidence is lacking. Therefore, we investigated the effects of high intake of fructose or galactose, with/without fructooligosaccharides (FOS), on gut microbiota composition in rats and explored the association between gut microbiota and low-grade systemic inflammation. Sprague-Dawley rats (n=6/group) were fed the following isocaloric diets for 12 wk (% of the dry weight of the sugars or FOS): 1) starch (control), 2) fructose (50%), 3) galactose (50%), 4) starch+FOS (15%) (FOS control), 5) fructose (50%)+FOS (15%), and 6) galactose (50%)+FOS (15%) 7) starch+olive (negative control). Microbiota composition in the large intestinal content was determined by sequencing amplicons from the 16S rRNA gene. 341F and 805R primers were used to generate amplicons from the V3 and V4 regions. Actinobacteria, Verrucomicrobia, Tenericutes, and Cyanobacteria composition differed between diets. Bifidobacterium was significantly higher in all diet groups where FOS was included. Modest associations between gut microbiota and metabolic factors as well as with gut permeability markers were observed, but no associations between gut microbiota and inflammation markers were observed. We found no coherent effect of galactose or fructose on gut microbiota composition. Added FOS increased Bifidobacterium but did not mitigate potential adverse metabolic effects induced by the sugars. However, gut microbiota composition was associated with several metabolic factors and gut permeability markers which warrant further investigations.